Efficacy of Elemental Sulfur Fertilizers. Issue 1 (8th December 2022) - Bremer, Eric
Abstract: Elemental sulfur (S) is produced in large quantities in both the U.S. and Canada as a by‐product of fossil fuel production. However, this form of S must be oxidized to sulfate (SO4 2– ) by soil microorganisms before crops can utilize it and therefore may not meet crop S requirements in the year of application. Rapid oxidation can be obtained if elemental sulfur particles are less than 20 μm in size and effectively dispersed in soil under favorable moisture and temperature conditions. Earn 0.5 CEUs in Nutrient Management by reading the article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses .